Multimodality Imaging in the Evaluation of Cardiovascular Manifestations of Malignancy - Laura Jiménez-Juan; Jessica Leen; Rachel M. Wald; Elsie T. Nguyen; Andrew T. Yan; Anish Kirpalani; Bernd J. Wintersperger; Andrew M. Crean (Cardiology Research and Practice)
Up to one third of the population will die as a direct result of cancer. Accurate and timely diagnosis of disease often requires multiple different approaches including the use of modern imaging techniques. Prompt recognition of adverse consequences of some anti-cancer therapies also requires a knowledge of the optimum imaging strategy for the problem at hand. The purpose of this article is to review not only some of the commoner cardiovascular manifestations of malignancy but also to discuss the strengths, weaknesses and appropriate use of cardiovascular imaging modalities.